Kajian Pengembangan Konten Digital Perpustakaan untuk Media Sosial: Perspektif Perpustakaan Nasional di Asia - Yaya Ofia Mabruri; Agus Triyanto (Perpustakaan Nasional, 2022)
The challenge for libraries in the digital era is the millennial generation's change in behaviour in accessing information, they access the information from any channels such as social media. Many libraries have used social media, especially Instagram, but their management is not optimal. This study aims to describe the trend of Instagram content development, user engagement analysis and explore the organisation's point of view on content development. This study uses quantitative method by examining 13 Instagram accounts of National Libraries in Asia in 6 months (January-June 2022). Based on 2,128 contents, known that Thailand (17.5%), Malaysia (15.8%), Indonesia (13.5%), UAE (11.4%), Singapore (9.7%), Korea South (6.7%), Armenia (5.4%), Maldives (5.1%), Hong Kong (4.2%), Azerbaijan (4%), India (3%), Qatar (2.8 %) and Uzbekistan (0.8%). Based on the form of news, 86.7% are text-image, while 13.3% are text-video. Video gets the most significant average likes and comments. Based on the type of service, 40.9% related to events, 36.1% references, 19.2% about public relations, 2.9% user education, and 0.9% circulation. Based on the type of visualisation, showcasing content is most often uploaded by 72.2%, humanising by 10.4%, interacting by 9.8%, crowdsourcing by 5.1%, placemaking by 1.8%, and orienting by 0.7%. Placemaking gets the most likes, and crowdsourcing receives the most extensive average comments. Instagram is used to build communication with users, share library information, and build images. Through this study, librarians are expected inspiration from the repertoire of social media content and development opportunities.